Online Reputation Evaluation of E-commerce Enterprises Based on Fuzzy Theory. (April 2020) - Li, Ying; Ning, Xiuli; Xu, Yingcheng; Lu, Xiaowei; Han, Lei
Abstract: With the development of network communication technology, the Internet technology is no longer the main factor restricting the development of e-commerce. While e-commerce facilitates people's daily life, the amount and quantity of transactions have greatly increased, and the risks arising from the virtuality of transactions have also increased dramatically. The author, with the construction of online reputation evaluation index system of e-commerce enterprises, comprehensively evaluates the online reputation of e-commerce enterprises with transactions carried out at their self-built platforms, by means of fuzzy analytic hierarchy process (AHP). Through practical application, this paper provides technical support for online reputation evaluation of e-commerce enterprises.